Endoscopic evaluation of surgically altered bowel in inflammatory bowel disease: a consensus guideline from the Global Interventional Inflammatory Bowel Disease Group - Shen, Bo; Kochhar, Gursimran S; Navaneethan, Udayakumar; Cross, Raymond K; Farraye, Francis A; Iacucci, Marietta; Schwartz, David A; Gonzalez-Lama, Yago; Schairer, Jason; Kiran, Ravi P; Kotze, Paulo Gustavo; Kobayashi, Taku; et al. (The lancet. Gastroenterology & hepatology, 2021)
The majority of patients with Crohn's disease and a proportion of patients with ulcerative colitis will ultimately require surgical treatment despite advances in diagnosis, therapy, and endoscopic interventions. The surgical procedures that are most commonly done include bowel resection with anastomosis, strictureplasty, faecal diversion, and ileal pouch. These surgical treatment modalities result in substantial alterations in bowel anatomy. In patients with inflammatory bowel disease, endoscopy plays a key role in the assessment of disease activity, disease recurrence, treatment response, dysplasia surveillance, and delivery of endoscopic therapy. Endoscopic evaluation and management of surgically altered bowel can be challenging. This consensus guideline delineates anatomical landmarks and endoscopic assessment of these landmarks in diseased and surgically altered bowel.
Keywords: Digestive System Surgical Procedures; Endoscopy; lidé; Middle Aged; Adult; Crohn Disease; Proctocolectomy, Restorative; Intestines; Recurrence; konsensus; Consensus; stupeň závažnosti nemoci; Crohnova nemoc; endoskopie; Colitis, Ulcerative; Humans; anastomóza chirurgická; stenóza; recidiva; Colonic Pouches; Anatomic Landmarks; anatomická značka; Inflammatory Bowel Diseases; lidé středního věku; Practice Guidelines as Topic; Constriction, Pathologic; chirurgie trávicího traktu; střeva; idiopatické střevní záněty; proktokolektomie rekonstrukční; pouch; Severity of Illness Index; směrnice pro lékařskou praxi jako téma; ulcerózní kolitida; dospělí; Anastomosis, Surgical